Knowledge and practices on solid waste management in students of a public university in Peru - Urure Velazco, Isabel Natividad (2024)
Solid waste management is a problem common to all institutions and also to the university. The objective was to determine the level of knowledge and practices on solid waste management in university students from a public university in Peru. The study was non-experimental, quantitative, correlational and prospective, with a sample of 228 students, using 2 nationally validated questionnaires as an instrument, adapted to our reality, with Kuder-Richardson reliability of 0.755 and Alpha Cronbach 0.823 for knowledge and practice respectively. Within the results, the age group of 20-24 years (86%), and the female sex (89%) predominated. Knowledge about solid waste was medium level 62.3%, the question with the highest accuracy according to the arithmetic average was the recovery of solid waste (X ? = 0.92, DS 0.25), and the one with the least success was the generation of solid waste (X ? = 0.34, SD 0.47). The practices on solid waste management were of a good level 71.5%, the most performed practice was using a cloth bag to make purchases (X ? = 4.07, DS 1.27). A very low negative correlation was found between the study cycle and the level of knowledge and practices (p<0.05), no significant relationship was found with age, sex and marital status (p>0.05). It is concluded that the relationship between knowledge and solid waste practices is significant and behaves in a moderately positive way (r = 0.412, p = 0.000), that is to say that, at a higher level of knowledge, solid waste management practices are better.